Comparative analysis of cervical cytology and human papillomavirus genotyping by three different methods in a routine diagnostic setting. Issue 5 (September 2015) - Padalko, Elizaveta; Ali-Risasi, Catherine; Mesmaekers, Stéphanie; Ryckaert, Inge; Van Renterghem, Lieve; Lambein, Kathleen; Bamelis, Mieke; De Mey, Anja; Sturtewagen, Yolande; Vastenavond, Hilde; Broeck, Davy Vanden; Weyers, Steven; et al.
<x xml:space="preserve">Abstract</x> Application of Bethesda guidelines on cervical cytology involves human papillomavirus (HPV) determinations on all ASC-US and ASC-H results. We compared HPV DNA results in view of the eventual development of a cervical intraepithelial neoplasia lesion determined either on cytology or histology. A total of 214 liquid-based cytology samples were analysed. Three different HPV DNA methods were applied: the Abbott RealTime High Risk HPV test, INNO-Lipa HPV Genotyping Extra and Full Spectrum PCR HPV Amplification and Detection/Genotyping System by Lab2Lab Diagnostic Service. A comparison of these three methods showed full concordance only for 49 samples (23%), and 27 (13%) of the samples were discordant in indicating the presence of the high-risk HPV type. Out of 214 patients, 88 were selected who presented with a cervical intraepithelial neoplasia or a VAIN lesion at follow-up cytology or histology. In this group, full concordance with HPV genotyping was present only in 19 (22%) follow-up samples. Nine (10%) follow-up samples showed discordant results for the presence of a high-risk genotype between the three genotyping methods tested either by negativity for high-risk HPV by one of the methods (n=6) or by failure to genotype HPV (n=2), or by a combination of both (n=1). Moreover, discordance for the detection of HPV16 or HPV18 was observed between the three HPV DNA genotyping methods used in 9 (10%) follow-up samples. In addition, the performance of genotyping methods on 20 external quality samples was assessed, showing discordant results for HPV16 and HPV18. Major differences were found in the genotyping results according to the HPV DNA method. Our findings highlight the importance of careful interpretation of data from studies using different HPV genotyping methods and underline the need for standardization by method validation in clinical laboratories, especially in the setting of primary HPV screening.